Introduction to Nanorobotic Manipulation and Assembly - Xi, Ning; Li, Guangyong (Artech House series nanoscale science and engineering, 2011)
Nanotechnology will allow us to build devices smaller than previously thought possible and will bring fundamental changes to disciplines within engineering, chemistry, medicine, biology, and physics. Understanding the principles of nano manipulation and assembly is tremendously important for those aiming to develop nanoscale systems. This forward-looking resource offers you cutting-edge coverage of the fundamentals and latest applications in this burgeoning field from an engineering perspective. The book shows you how nano-manipulation allows for the detection and manipulation of tiny entities such as single molecules, nanotubes, nanocubes, cells, viruses, proteins, and DNA molecules. You discover the most promising nanorobotic manipulation and assembly methods and find clear examples of key application areas, including nano sensors, electronics, and biomedical engineering. Supported with over 100 illustrations, this groundbreaking volumes offers comprehensive coverage of the subject, from the physics of nano manipulation, to robotic assembly of nano devices. Moreover, you get a glimpse of the future direction of this revolutionary technological area.